2006
DOI: 10.1111/j.1469-0691.2006.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of methicillin-resistant Staphylococcus aureus ST80, novel ST125 and SCCmecIV in the south-eastern part of Norway during a 12-year period

Abstract: A retrospective population-based study of genotypes of methicillin-resistant Staphylococcus aureus (MRSA) was performed during the period 1991-2003 in two counties in the south-eastern part of Norway. Isolates of MRSA from all individuals in the two counties in whom MRSA was detected were genotyped by means of multilocus sequence typing (MLST), staphylococcal cassette chromosome mec (SCCmec) typing, staphylococcal protein A gene (spa) typing and amplified fragment length polymorphism (AFLP) analysis. Until 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 31 publications
5
40
0
2
Order By: Relevance
“…This clone emerged in Spain during 1996, although it was first reported in 2001, and has now become predominant in Spanish hospitals (46,47,56). At a lower frequency, it was also found in Norway (13). As in the present study, a strong correlation between ST125 and spa type t067 was observed in both countries.…”
Section: Discussionsupporting
confidence: 71%
“…This clone emerged in Spain during 1996, although it was first reported in 2001, and has now become predominant in Spanish hospitals (46,47,56). At a lower frequency, it was also found in Norway (13). As in the present study, a strong correlation between ST125 and spa type t067 was observed in both countries.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, in the present study (conducted with strains collected in 2006), we identified the same predominant clones as well as two new clones, E19 (ST8) and E20 (ST125), with the latter clone being closely related to the predominant E7 and E8 clones. These genotypes belong to ST125, which continues to be responsible for more than half of the nosocomial MRSA infections in Spain (59.3%), although it is unusual in the rest of Europe (23,42). Our results validate the use of PFGE for long-term nationwide epidemiological studies, although we consider that this technique presents difficulties in interlaboratory reliability.…”
Section: Discussionsupporting
confidence: 58%
“…spa typing was performed as described previously (1). Assignment of spa type and Based Upon Repeat Pattern (BURP) analysis for assignment of spa clonal complexes (CCs) were performed using Ridom StaphType v.2.0.3 (http://www.ridom.de).…”
mentioning
confidence: 99%